Explanatory Factors of the Expansion of Recreation Function on the Bank of Danube River in Budapest - Pál Szabó; Zoltán Mihályi; Tamás Szomorjai; Emese Tóth (DETUROPE)
In a city's development a river and riverbank played important role, however in recent decades the functions of them have changed, transformed, especially in major cities in the more developed countries, so the city administration was faced with a new phenomenon and geographical space: the changing riverbanks, and the utilization, development, revitalization of them has become a key issue. The various real processes showed the direction that these areas should be provided to the people, and the recreation service will be important for the local residents and tourists. Overall, the urban waterfront development is an increasingly important researched topic and policy. The question is: can we realize it in Budapest also nowadays? In recent years, those processes took place in Budapest, which resulted in an increasing utilization of the Danube and its banks for recreational functions. On the one hand, local social and economic processes have led to the waterfront sites released, on the other hand the needs of the residential population and tourists using the river and the riverside for recreational purposes have increased, and thirdly, the new city administration decided to renew the banks of the Danube, mainly to create new recreational areas. In this paper, we analyze these three factors, focusing on a past short period, because there is an exceptional cohesion between the processes, the needs and the new development goals. Two case studies are in the paper also: the Margaret Island as the oldest traditional recreational area in Budapest, and the Kopaszi-dam, as the newest and successful recreational area of Budapest. The analysis of the processes is based on data and literature, the analysis of the needs is based on a survey, and the analysis of the goals is based on the different development documents.